(untitled) (Revista Archai, 2016)
Inasmuch as it has in its core the power of the “crowd”, democracy rests on a concept which is directly and explicitly opposed to philosophy: philodoxy. While a well-ordered polis lies, according to Plato, in the power of those who have “the art of ruling”, and philosophy leads to the acquisition of this art, democracy is based on the power of those who are not qualified to rule, i.e. on the power of those who are able to manipulate their opinion (doxa). Starting from the opposition between philosophy and philodoxy, between the “love of knowledge” and the “love of opinion”, the present paper approaches the conception of philosophy as an alternative political project to democracy.